Evaluating Alternative-Fuel Busses for Public Transportation in Istanbul Using Interval Type-2 Fuzzy AHP and TOPSIS - Erdogan, Melike; Kaya, Ihsan (OLD CITY PUBLISHING INC, 2016)
The use of alternative-fuel busses will help to reduce environmental and health risks due to air pollution significantly. To select which of the alternative-fuel busses will be used in public transportation is a kind of decision making problem. In this paper, a multi criteria decision making (MCDM) methodology based on type-2 fuzzy sets is proposed to manage qualitative and quantitative criteria with uncertainties for selecting the best alternative fuel bus for public transportation in Istanbul. The proposed MCDM methodology consists of three techniques named Delphi Methodology, AHP and TOPSIS. We carried out a real case application to draw attention for exhaust gases from the increasing number of motor vehicles as the major factor of air pollution in Istanbul. For this aim, five criteria and sixteen sub-criteria have been used in this paper to evaluate four alternative-fuel busses in Istanbul. As a result, alternative-fuel busses have been selected to use public transportation in Istanbul with the least impact on environmental pollution. The alternative bus that uses compressed natural gas (CNG) is determined as the best alternative for public transportation in Istanbul.
Keywords: Alternative-fuel busses; Delphi methodology; interval type-2 fuzzy AHP; interval type-2 fuzzy TOPSIS; environmental protection; AXIOMATIC DESIGN; LOCATION SELECTION; AIR-POLLUTION; DELPHI METHOD; HEALTH-RISKS; SECTOR; HYDROGEN; Computer Science; Science & Technology - Other Topics